The Impact of Marketing Strategy on Herbicide Utilization by Rice Cultivators - Nasir; Gusti Fitriyana; Wiwin Dian Pertiwi; Sisva Berti Afriatna; Nurlaili Fitri Gultom; Sri Rahayu Endang Lestari (Universitas Muhammadiyah Palembang, 2025)
Intense competition among herbicide manufacturers requires companies to implement various marketing strategies so that their products can be accepted by farmers. The marketing strategies implemented potentially influence the level of herbicide adoption by farmers. This research aims to: (1) determine the effectiveness of herbicide marketing strategies towards rice farmers; (2) analyze the level of herbicide adoption by rice farmers; and (3) examine the effect of marketing strategies on the adoption of herbicides by rice farmers. The research method used is the survey method. Sampling was carried out using the simple random sampling technique. Data processing was performed using qualitative and quantitative methods. The qualitative method was used to answer the first and second problems through descriptive analysis, while the quantitative method was used to answer the third problem using multiple regression analysis. The results of the study indicate that: (1) The marketing strategy through offline promotion is effective in delivering information about the gramoxone herbicide to farmers, while online promotion is quite effective in providing information about the herbicide; (2) the level of Gramoxone herbicide adoption by rice farmers in Telang Jaya Village, Muara Telang District, Banyuasin Regency is classified as high; and (3) marketing strategies through offline promotion significantly influence herbicide adoption, while online promotion does not significantly affect the adoption of herbicides by farmers.